The 'polymeric' structure of BeCl2 from an ionic simulation model - Wilson, M; Madden, P (1997)
A polarizable ionic potential for BeCl2 is obtained from potentials developed previously to represent other group IIa chlorides, simply by scaling the cation radii. The BeCl2 potential reproduces the known structure of the isolated molecule and crystal and is used in simulations of the melt and molten mixtures with the 'network modifier' KCl. The simulations show that the quasi-polymeric molecules, consisting of chains of edge-sharing BeCl4 tetrahedra, which are known in the crystal, persist as chains of finite length in the melt. The physical factors responsible for the emergence of such local structure for an ionic interaction model are discussed. The addition of the network modifier causes the molecular chains to break down into a mixture of ionic species. The evolution of this process, as observed in the experimental Raman spectra, is reproduced successfully by that of certain projected vibrational densities of states in the simulation.